The bitter side of epigenetics: variability and resistance to chemotherapy - Hajji,N; García-Domínguez,DJ; Hontecillas-Prieto,L; O'Neill,K; de,Álava E; Syed,N (Epigenomics, 2021)
One of the major obstacles to the development of effective new cancer treatments and the main factor for the increasing number of clinical trial failures appears to be the paucity of accurate, reproducible and robust drug resistance testing methods. Most research assessing the resistance of cancers to chemotherapy has concentrated on genetic-based molecular mechanisms, while the role of epigenetics in drug resistance has been generally overlooked. This is rather surprising given that an increasing body of evidence pointing to the fact that epigenetic mechanism alterations appear to play a pivotal role in cancer initiation, progression and development of chemoresistance. This resulted in a series of clinical trials involving epi-drug as single treatment or combined with cancer conventional drugs. In this review, we provided the main mechanisms by which the epigenetic regulators control the resistance to cancer drugs.